Correction: Iron-based clusters embedded in nitrogen doped activated carbon catalysts with superior cathodic activity in microbial fuel cells. Issue 21 (19th May 2020) - Zhang, Xiaoyuan; Guo, Xingguo; Wang, Qiuying; Zhang, Rufan; Xu, Ting; Liang, Peng; Huang, Xia
Abstract : Correction for 'Iron-based clusters embedded in nitrogen doped activated carbon catalysts with superior cathodic activity in microbial fuel cells' by Xiaoyuan Zhang et al., J. Mater. Chem. A, 2020, DOI: ; 10.1039/C9TA10797E .